Comparison of the effects of chronic intra-articular administration of tenoxicam, diclofenac, and methylprednisolone in healthy rats - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: Lyophilized drug manufacturing and intra-articular (IA) applications have increased to address gastrointestinal side effects resulting from chronic treatment with non-steroidal anti-inflammatory drugs (NSAIDs) for degenerative joint disease. Accordingly, we histologically examined joint and stomach tissues from rats to determine and compare the effects of long-term treatment with an IA corticosteroid (methylprednisolone acetate), lyophilized NSAID (tenoxicam), and non-lyophilized NSAID (diclofenac) following application to the knee joint. Methods: One hundred Wistar albino rats were divided into 4 groups of 25 rats: control, methylprednisolone, tenoxicam, and diclofenac. Ten IA injections were administered at 1-week intervals. Rats were sacrificed at 48 h and 1, 2, 4, and 8 weeks after the tenth injection. Histomorphologically, knee joint samples were examined for osteoarthritic changes and stomach tissue samples for gastric changes. Results: Unlike methylprednisolone, diclofenac and tenoxicam caused increased fibrosis and fibroblast production; furthermore, chronic methylprednisolone use had no negative effects on the synovium or cartilage. Conclusion: Chronic tenoxicam and diclofenac use affects joints more negatively than chronic steroid treatment.
Keywords: Diclofenac; experimental study; intraarticular; methylprednisolone; tenoxicam; ANTIINFLAMMATORY DRUGS; ARTICULAR-CARTILAGE; STEROID INJECTIONS; DOUBLE-BLIND; OSTEOARTHRITIS; KNEE; ARTHROSCOPY; HYALURONATE; ANALGESIA; THERAPY